"Artificial intelligence", or statistics?. Issue 4 (24th July 2019) - Lowe, David
Abstract : Professor David Lowe briefly explains the statistical underpinnings of AI Abstract : Professor David Lowe briefly explains the statistical underpinnings of AI.